Cephalometric evaluation of changes in vertical dimension and molar position in adult non-extraction treatment with clear aligners and traditional fixed appliances - Hailee RASK; Jeryl D. ENGLISH; Clark COLVILLE; Fred Kurtis KASPER; Ronald GALLERANO; Helder Baldi JACOB (Dental Press Editora, 2021)
ABSTRACT Introduction: Orthodontists have been using clear aligners to treat malocclusions, and one potential effect of treatment with orthodontic aligners is the intrusion and/or resists extrusion of the posterior teeth. This "bite-block effect" is primarily anecdotal due to the frequent occurrence of posterior open bites in patients after clear aligner therapy. Objective: The purpose of this study was to compare changes promoted by clear aligners and traditional fixed appliances in cephalometric measurements of the vertical dimension and molar position in adult patients with Class I malocclusion treated with non-extraction. Methods: Pre- and post-treatment lateral cephalometric radiographs of adult patients treated with either clear aligners (n=44) or traditional fixed appliances (n=22) were selected for retrospective analysis. Eight interval measurements and one nominal measurement were evaluated: anterior overbite (OB), mandibular plane angle related to cranial base (SN_MP) and related to Frankfort (FMA), lower molar height (L6H) and upper molar height (U6H), palatal plane to mandibular plane angle (PP_MP), lower facial height (LFH), total facial height (TFH), and posterior open bite (Posterior_OB). A single evaluator traced all cephalographs, and changes in select measures of the vertical dimension were compared within and between groups. Results: OB decreased (1.15 mm) and L6H increased (0.63 mm) in the traditional fixed appliance group. Mandibular plane angles (related to cranial base and to Frankfort) increased (0.43° and 0.53°, respectively) in the clear aligner group, but just FMA showed significant difference between groups (difference of 0.53°). LFH and TFH increased (ranging from 0.52 mm to 0.80 mm) in both groups, with no differences between treatment modality. Presence of visible posterior open bite significantly increased over the course of treatment. OB, FMA and L6H exhibited an interaction between treatment stage (pre- and post-treatment) and modality (clear aligner therapy and traditional fixed appliances), but no interaction among these three variables was found. Conclusions: The evidence does not support the theory that clear aligner therapy produces better vertical dimension control than traditional fixed appliances. Traditional fixed appliance therapy slightly extruded the lower molar, and clear aligner therapy produced a slightly mandibular backward rotation.